Role of Grina/Nmdara1 in the Central Nervous System Diseases - Chen, Kai; Yang, Liu N.; Lai, Chuan; Liu, Dan; Zhu, Ling-Qiang (Current Neuropharmacology, 2020)
Glutamate receptor, ionotropic, N-methyl-D-aspartate associated protein 1 (GRINA) is a member of the NMDA receptors (NMDARs) and is involved in several neurological diseases, which governs the key processes of neuronal cell death or the release of neurotransmitters. Upregulation of GRINA has been reported in multiple diseases in human beings, such as major depressive disorder (MDD) and schizophrenia (SCZ), with which the underlying mechanisms remain elusive. In this review, we provide a general overview of the expression and physiological function of GRINA in the central nervous system (CNS) diseases, including stroke, depression ,epilepsy, SCZ, and Alzheimer’s disease (AD).
Keywords: depression